Standards of Child Resistant Packaging: A Regulatory View - Gowthami Kodlahalli Ravindra
Special packaging known as (3z(Bchild-resistant packaging(3y (Bis intended to minimize the possibility of kids eating harmful substances. The Poison Prevention Packaging Act of 1970 confers jurisdiction to regulate this on the U.S. Consumer Product Safety Commission and amended in 1995 to include senior-friendly packaging which became effective in 1972.s